Changing Perceptions of Alexander in French Chronicles. Issue 1 (2nd January 2019) - Stones, Alison
ABSTRACT: This article surveys the various pictorial treatments of Alexander in French historical compendia from the twelfth to fifteenth centuries, focusing on three traditions: Lambert of Saint-Omer's Liber floridus ; Vincent of Beauvais' Speculum historiale, in Latin and in the French translation by Jean de Vignay, and Jean de Courcy's La Bouquechardière . In all these texts the presence of pictures and the subjects chosen reflect what was thought about the relative importance of the accompanying text. Shifts in the choices of episodes selected for illustration, and changes in the patterns of patronage, from ecclesiastical figures to members of the royal, noble, and finally governing classes, many of them women, denote a continued and evolving interest in Alexander as an important figure of history and legend.